Guidelines for Hiring a Florida-Friendly Landscape Professional - Esen Momol; Claire Lewis; Tom Wichman; Elisha Cash; Jen Marvin; Michelle Atkinson; Julie McConnell; Tina McIntyre; Chris Marble; Bryan Unruh; Lynn Barber; Stacie Greco; et al. (EDIS, 2022)
Many residents evaluate their landscape professionals on price alone; however, quality landscaping is an investment in your property. Knowing what to look for in a landscape professional will help you get the most for your investment, ensure your yard reaches its greatest potential and protect Florida’s water and other natural resources. This new 7-page document, published by the UF/IFAS Environmental Horticulture Department, is intended to provide guidance to residents and entities such as HOA community associations when hiring a landscape professional. https://edis.ifas.ufl.edu/ep614